PENERAPAN MODEL PEMBELAJARA LANGSUNG UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS VB SDN 165 PEKANBARU - Marhadi, Hendri; ', Muhairah; ', Syahrilfuddin (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract :This study was not optimal background science student learning outcomes, of the 37 students there are 22 students (59.5%) who have not yet reached KKM. The research problems are